The development and validation of the health literacy questionnaire for kindergarten teachers - Han Ying; Yang DeHua; Ou Yang Yi; Wu Song-Wei (Frontiers in Public Health, 2025)
BackgroundHealth literacy profoundly influences individuals’ health development. As pivotal figures in shaping young children’s well-being and delivering health education in kindergartens, kindergarten teachers are essential. Yet, assessing their health literacy remains challenging due to a scarcity of evaluation tools.MethodsBased on existing research, the initial questionnaire was developed through interviews, summaries, and reviews. A total of N = 120 (Mage = 27.19, SD = 6.75, 94.2% female) kindergarten teachers participated in item analysis and exploratory factor analysis (EFA). N = 642 (Mage = 28.12, SD = 5.77, 89.7% female) kindergarten teachers were involved in confirmatory factor analysis (CFA) and reliability analysis.ResultsThe questionnaire on the health literacy of kindergarten teachers consists of 30 items in four dimensions: health concept, health behavior, health ability, and health knowledge. In the EFA, the cumulative variance contribution rate reached 61.220%. The CFA indicators satisfied the fit criteria, indicating a well-fitted model (χ2/df = 1.945, CFI = 0.956, TLI = 0.952, SRMR = 0.034, RMSEA = 0.038). The reliability analysis indicated that Cronbach’s α, McDonald’s ω, and split-half reliability all exceeded 0.8.ConclusionThe Health Literacy Questionnaire for kindergarten teachers, with its strong reliability and validity, serves as a valuable assessment tool for this group’s health literacy.